Notes on Arthur Grimble's a pattern of Islands (Methuen, 1972)
Arthur Grimble was sent to the Gilbert and Ellice islands as a colonial administrator in the twilight of the Edwardian era. He lived there for the next twenty-five years and developed a rare passion for the language, life and landscape of the place. Fortunately his island neighbours, a fascinating cast of fishermen, sorcerers, poets and fighters, began to trust this charming, happy and energetic young man, and shared with him their treasury of stories from the days when warfare was endemic and magic an essential part of everyday life.